Komparasi Hasil Belajar Fiqih Qur-any antara Siswa Lulusan SD dengan MI Kelas VII C di MTs Al-Urwatul Wutsqo Jombang - Moch Sya'roni Hasan (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2022)
The problems that will be studied in this research are there differences in learning outcomes for Qur-any subjects (Tafsir Ahkam) between students who graduated from elementary school and students who graduated from MI in class VII male MTs Al-Urwatul Wutsqo Bulurejo Diwek Jombang? The population and sample in this study were male students of MTs grade VII at MTs Al-Urwatul Wutsqo Jombang. With a population of 36 students. The samples taken were 18 students from elementary schools and 18 students from Madrasah Ibtidaiyah. The analysis used is comparative analysis, with the